Trends in Pain Medicine Liability. (November 2015) - Pollak, Kelly A.; Stephens, Linda S.; Posner, Karen L.; Rathmell, James P.; Fitzgibbon, Dermot R.; Dutton, Richard P.; Michna, Edward; Domino, Karen B.
Abstract : Background: The authors examined changes in the frequency of pain medicine malpractice claims and associated treatment modalities and outcomes over time. Methods: The authors analyzed trends in pain medicine claims from 1980 to 2012 in the Anesthesia Closed Claims Project database by binary logistic regression on year of event. Pain procedures in claims from 2000 to 2012 were compared with the proportion of pain procedures reported to the National Anesthesia Clinical Outcomes Registry in 2010–2014. Results: Malpractice claims for pain medicine increased from 3% of 2, 966 total malpractice claims in the Anesthesia Closed Claims Project database in 1980–1989 to 18% of 2, 743 anesthesia claims in 2000–2012 (odds ratio [OR], 1.088 per year; 95% CI, 1.078 to 1.098; P < 0.001). Outcomes in pain claims became more severe over time, with increases in death and permanent disabling injury (OR, 1.094 per year; P < 0.001). Nonneurolytic cervical injections increased to 27% of pain claims in 2000–2012 (OR, 1.054; P < 0.001), whereas National Anesthesia Clinical Outcomes Registry demonstrates that lumbar injections are a more common procedure. Claims associated with medication management increased to 17% of pain claims in 2000–2012 (OR, 1.116 per year; P < 0.001). Conclusions: Pain medicine claims have increased over time and have increased in severity. Claims related to cervical procedures were out of proportion to the frequency with which they are performed. These liability findings suggest that pain specialists should aggressively continue the search for safer and more effective therapies. Abstract : In a review of the Anesthesia Closed Claims Project database, the proportion of malpractice claims in pain medicine increased from 3% in 1980–1989 to 18% in 2000–2012, accompanied by increasing severity of injury, including death and permanent disabling injury. Claims related to cervical procedures were out of proportion to the frequency with which they are performed.